DEVELOPING A CHARACTER BASED ENGLISH LANGUAGE TEXTBOOK FOR GRADE IX OF JUNIOR HIGH SCHOOL BASED ON THE CURRICULUM 2013 - ., Wulan Trisna Siska; ., Drs.Gede Batan,MA; ., Ni LP. Eka Sulistia Dewi, S.Pd. M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
ABSTRACT This research aimed at developing a character based English language textbook for grade IX of junior high school based on the curriculum 2013. This study was designed by modifying the research and development model proposed by Dick, Carey and Carey (2001). There were 11 stages involved in this research, namely 1)identifying instructional goal, 2)conducting instructional analysis, 3)analyzing learner and context, 4)writing performance objectives and indicators, 5)developing judgment rubric, 6)developing design of the textbook, 7)developing content of the textbook, 8)conducting formative evaluation, 9)revising the textbook, 10)limited field trial, 11)final product. This study involved 30 students of SMP Laboratorium Undiksha class IX-1 as the research subjects and an English teacher as well as a lecturer who masters material development as expert judges in assessing the textbook quality. The result of the study shows that the character building was inserted in terms of content and presentation in the textbook. By following the curriculum 2013, the stages of scientific approach were inserted in the presentation of the textbook. Based on the result of the experts’ judgment, it is found that value of Cronbach’s Alpha is 0.850 which indicates good reliability. Moreover, the textbook feasibility is convinced by the mean score from the expert judgment that showed result of 4.55 which categorized as excellent. Besides that, the results of post-questionnaire shows that 90% students are happy in using the textbook. Thus, the character based English language textbook is feasible to be used for grade IX of junior high school based on curriculum 2013. keyword : English textbook, character-based instruction, curriculum, curriculum 2013